A new energy‐compatible nonstationary stochastic ground‐motion simulation method. (23rd January 2021) - Wang, Shaoqing; Yu, Ruifang; De Risi, Raffaele; Li, Xiaojun
Abstract: A new time‐frequency modulating function with a novel equivalent average‐intensity envelope based on the instantaneous energy is proposed to simulate fully nonstationary ground motions. The new model utilizes simple, uncoupled, and statistically well‐studied temporal and spectral nonstationary parameters. Then, a period‐by‐period simulation method based on the proposed stochastic model is developed to match multiple targets. A numerical comparison shows that the new method replicates well both the target temporal and spectral nonstationarities and it is efficient and easy to use in engineering practice. This study also demonstrates that for obtaining site‐specific seismic input by means of site response analysis: (1) the frequency contents of bedrock motion, including the energy concentration in terms of frequency and frequency decaying with respect to time, have a significant impact on the site response with moderate and large PGA levels; (2) using the proposed instantaneous‐frequency‐related time modulating function to approximate the real ground motion leads to results sufficiently close to the record for nonlinear site response regardless PGA levels and site condition. Therefore, attention should be paid to the change of nonstationary characteristics of ground‐motion frequency according to the source, path, and site condition when simulating ground motion on bedrock. As the proposed methods can approximately control various ground‐motion characters, different targets of ground‐motion simulation can be matched for different engineering purpose such as site response analysis, time‐history analysis of special structures, etc.